IDENTIFIKASI POTENSI BULLYING DAN PENCEGAHANNYA PADA PESERTA DIDIK MADRASAH IBTIDAIYAH - Ida Fitri Shobihah (LP3M Universitas Islam Zainul Hasan Genggong, 2024)
Students at Madrasah Ibtidaiyah (MI) level are children and are still in the stage of developing cognitively, emotionally and socially. Bullying is a negative action that often occurs at all levels of education. As a first step in prevention, it is necessary to identify potential perpetrators of bullying in MI level students and develop an effective implementation plan to stop potential bullying in children. The research was conducted using qualitative research methods with 2 research stages. The first stage is to identify potential bullying and the second stage is to plan prevention activities and implement them. The results of the research show that there are 11 potential forms of bullying among MI level students and there are 3 forms of bullying prevention activities that are easy to put into practice and have quite good effectiveness. Keyword: potensial of bullying, prevention, students at MI